Dinámicas de anotación de goles en las cinco grandes ligas europeas de fútbol: Efectos situacionales y del sexo en el resultado del partido - Almeida, Carlos Humberto; Paixão, Paulo; Jorge, José António; Vargas, Pedro; Gonçalves, Ricardo; Batalau, Rui (Retos, 2025)
Introduction: Despite recent advancements in understanding goal-scoring determinants in football, a noticeable research gap persists between women’s and men’s games, warranting more comprehensive studies. Aim: This retrospective observational study addressed this gap by examining how situational variables (country, match location, match period, numerical relation, team quality, and goal criticality) and sex influence the match outcome in the Big-5 European leagues across two seasons (2020/21–2021/22). Methods: All goals scored by male and female teams in top-tier divisions of English, Spanish, Italian, German, and French football (n = 15,366) were analysed through chi-square tests and multinomial logistic regression. Results: Bivariate analyses uncovered significant associations of all situational variables with the match outcome, except for the match period. Detailed results from regression models applied to women’s and men’s goals demonstrated varying influences of situational variables between them. Country-based differences shaped match results in women’s leagues. Moreover, women were more prone to be influenced by the complex interaction of context-related factors during match-play, arguably due to lower professionalism, skill level and competitive balance. Critical goals, which are predominantly scored in the first half, were found to be essential to favourable match outcomes. Nevertheless, scoring under critical circumstances (i.e., that change the competitive status between opposing teams) acquires greater importance as the match unfolds, especially in men’s football. Conclusion: As the game evolves, accommodating these insights will elevate performance and inform strategic decisions for coaches, players, and stakeholders. The pursuit of excellence in football demands a continual embrace of situational awareness.